The Zunis : Self-Portrayals - Quam, Alvina (Book collections on Project MUSE., 1972)
Now back in print after more than thirty years, The Zunis: Self-Portrayals offers forty-six stories of myth, prophecy, and history from the great oral literature of the Zuni Indians of New Mexico.